Improving Narrative Text Identification through Cooperative Learning with the NHT Technique - Mia Andriyani; Arini Vika Sari (PT. Mifandi Mandiri Digital, 2023)
This study aims to improve students' learning outcomes in identifying narrative texts using the Numbered Head Together (NHT) cooperative learning method for seventh-grade students at MTs Al Washliyah. This classroom action research was conducted in two cycles, with each cycle consisting of three meetings. The research setting was MTs Al Washliyah in Lubuk Pakam, and the study followed the Kemmis and Taggart model. The subjects of the study were 30 seventh-grade students, consisting of 13 male and 17 female students. Data collection techniques included collaborative observation and documentation, focusing on three aspects: cognitive, affective, and psychomotor. The research instruments used were: affective assessment format, student worksheets, and psychomotor assessment format. The data analysis technique employed was descriptive quantitative statistical analysis. The results indicated that the application of the Numbered Head Together (NHT) cooperative learning method, supplemented with PowerPoint media, successfully enhanced students' learning outcomes in describing narrative texts. This was evident from the improved student learning outcomes in each cycle. In cycle I, 17 students (57%) achieved mastery, while 13 students (43%) did not meet the Minimum Completion Criteria (KKM). In cycle II, the number of students meeting the KKM increased to 22 students (73%), with 8 students (27%) not meeting the KKM. These findings suggest that the Numbered Head Together (NHT) method significantly improved students' ability to identify narrative texts.